Willingness and Hesitancy to Vaccinate Against COVID-19 in People with Multiple Sclerosis - D. Bučaitė; J. Valinčiūtė; D. Mickevičienė (Neurologijos seminarai)
Introduction. During the pandemic, vaccination against COVID-19 has become one of the most important ways to prevent severe infection. However, a lack of trust in vaccines among the population, including people with multiple sclerosis (MS) has been identified. In Lithuania, the specific reasons for vaccine hesitancy among people with MS have not been described. We conducted a survey to determine the attitude of people with MS towards vaccination against COVID-19 infection.